Understanding farmers’ use of climate information services in Kenya: A human-centered design approach (Focus group discussion guide) - Giraldo Mendez, Diana Carolina; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This guide supports researchers and practitioners in facilitating participatory discussions with Kenyan farmers to explore how they access, trust, and use agricultural and climate information. Using a human-centered design approach, it captures gendered preferences, digital access, and decision-making processes to inform inclusive, user-driven climate service design and delivery.